Anticoagulation and the risk of complications in ventricular tachycardia and premature ventricular complex ablation. Issue 11 (26th September 2018) - Lane, Jem D.; Cannie, Douglas; Volkova, Elena; Graham, Adam; Chow, Anthony; Earley, Mark J.; Hunter, Ross J.; Khan, Fakhar; Lambiase, Pier D.; Schilling, Richard; Sporton, Simon; Dhinoja, Mehul
Abstract: Background: Many patients undergoing ventricular tachycardia (VT) or premature ventricular complex (PVC) ablation receive antithrombotic medications. Their uninterrupted use has the potential to affect complication rates. We assessed the incidence of complications in a large cohort of patients undergoing these procedures, according to antithrombotic medication use. Methods: From June 2014 to June 2016, 201 VT and PVC ablations were performed at a single center. We allocated patients to three groups: (A) anticoagulation group (international normalized ratio ≥ 1.5 or non‐vitamin K anticoagulant or full‐dose low‐molecular‐weight (LMW) heparin on day of procedure); (B) antithrombotic group (antiplatelet therapy and/or prophylactic LMW heparin on day of procedure); and (C) no antithrombotics group. We assessed periprocedural complication rates in each group. Multivariable analysis was performed. Results: Group A (47 patients) had 8.5% procedural complication rate: one stroke, one pseudoaneurysm, one femoral artery occlusion, and one access site hematoma. In this group, 37 patients had femoral arterial and 18 had epicardial access. In Group B (46 patients), the complication rate was 6.5%: two cardiac tamponades and one pericardial effusion without compromise. Group C (108 patients) had a 5.6% complication rate: three cardiac tamponades (with one periprocedural death and one concomitant gastric vessel injury), one pericardial effusion without compromise, one stomach perforation, and two access site hematomas. Multivariable analysis did not show any significant predictors of complications, though age approached significance. Conclusions: Complication rates were not significantly different between groups. These findings suggest that VT and PVC ablation can be performed safely in patients with uninterrupted antithrombotic medications.